Phonon effects on the dynamics and fidelity of two-qubit gates using trapped Rydberg ions - Aderiye, Phileo (2022)
Ultra-cold Rydberg ions confined in a linear trap are presented as a possible solution to some of the major problems causing infidlities currently presented in quantum computing gates e.g. weak two-body interactions such as magnetic field fluctuations. The dynamics and intrinsic fidelity of the controlled-Z gate are simulated using the Fock state |gg, 00i (where g and 0 denote the groundstates of the spin and phonon excitations respectively) of a two-qubit system, where the fidelity of the gate is found to be 0.9999472, satisfying the fidelity requirement for a scalable quantum computing gate of 0.9999. The same was done for phonon coherent states of the form |gg, α, αi, where the displacement operator takes the form D(α) = exp(αa† − α ?a). It is shown, to obtain the fidelity needed for a reliable individual quantum gate of at least 0.97, the maximum value for alpha is αmax = 0.25; to obtain the fidelity needed for a scalable quantum gate of at least 0.9999, the maximum value for alpha is αmax = 0.0525.